Effect of Cardiovascular Training on Functional Capacity in Post-Acute Rehabilitation of COVID-19 Patients - Dragicevic-Cvjetkovic, Dragana M; Stevandić, Drinka (Scripta Medica, 2021)
Introduction: In the overall strategy of developing the optimal treatment of patients after COVID-19 infection, recommended by the World Health Organization, rehabilitation plays one of the key roles in improving the functional capacity of these patients and thus their quality of life. The aim of this study was to investigate the effect of cardiovascular training during post-acute rehabilitation on the functional capacity of patients after moderate COVID-19 pneumonia. Methods: The prospective study included 84 patients of both sexes, mean age 57.92 ± 11.79 years, who were hospitalised at the Institute of Physical Medicine and Rehabilitation ’’Dr Miroslav Zotović’’ Banja Luka due to moderate pneumonia caused by the COVID-19 virus and after they finished acute rehabilitation. All patients underwent cardiovascular training three times per week and oc- cupational therapy during 28 days of stationary post-acute rehabilitation. The follow-up parameter was a six-minute walk (6-MWT) test at admission and discharge from post-acute rehabilitation. Student t-test for paired samples was used for statistical analysis, and the value of p < 0.05 was taken as statistical significance. Results: The functional capacity of the cardiovascular and respiratory system was statistically significantly improved at discharge compared to admission (p < 0.05). Conclusion: Targeted cardiovascular training during post-acute rehabilitation leads to improvement of functional capacities of patients after moderate COVID-19 pneumonia.